WORK-LIFE BALANCE IN INDIAN WORKPLACES: ROLE OF LABOUR REGULATIONS - Sharma, Deepankar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Work-life balance has become a critical issue in modern societies, reflecting the need for workers to manage their professional responsibilities while maintaining a fulfilling personal life. In India, the rapid pace of economic development, coupled with increasing urbanization and changing social dynamics, has made work-life balance a pressing concern. Labor regulations play a pivotal role in shaping the work environment and, by extension, the ability of workers to achieve a balanced life. This analysis explores the labor regulations in India, their impact on work-life balance, and the challenges and opportunities they present.